Power Contestation and Shadow Institutionalization: Explaning Healthy City Policy Sustainability in Indonesia - Yuni Purwani; Teguh Yuwono; Fitriyah Fitriyah; Nunik Retno Herawati; Hermawan Budiyanto (Greenation Research & Yayasan Global Resarch National, 2026)
The Healthy City (Kabupaten/Kota Sehat, KKS) programme in Indonesia presents a theoretically unresolved paradox: 39.5% of high-achieving districts experience programme discontinuity even under same-party leadership with the programme formally embedded in regional planning documents. This article proposes a novel analytical framework by integrating multidimensional power contestation theory (Lukes, 2005; Foucault, 1980) with gradual institutional change theory (Mahoney & Thelen, 2010), drawing illustratively on Semarang City a consecutive Wistara award recipient that failed national verification in 2023 under the same party leadership. Two conceptual contributions are advanced. First, the concept of shallow institutionalisation distinguishes programme formalisation (administrative compliance) from programme internalisation (genuine cultural change and community ownership). Second, a KKS sustainability model identifies three hierarchically ordered conditions: formalisation as necessary, internalisation as sufficient, and autonomous collaborative networks as protective. The article argues that conventional policy sustainability theory neglects intra-party elite circulation as a more deterministic explanatory variable than party affiliation per se. The framework contributes to institutionalism and governance literatures and carries practical implications for redesigning collaborative health programmes in decentralised governance contexts.